Adaptation of Color Reactions for Spectrophotometric Determination of Pitavastatin Calcium in Bulk Drugs and in Pharmaceutical Formulations - Marothu Vamsi Krishna; Dannana Gowri Sankar (E-Journal of Chemistry)
Three simple, sensitive and cost effective Spectrophotometric methods are described for the determination of pitavastatin calcium (PST) in bulk drugs and in pharmaceutical formulations. These methods are based on the oxidation of PST by ferric chloride in presence of o-phenanthroline (Method A) or 2, 2’ bipyridyl (Method B) or potassium ferricyanide (Method C). The colored complex formed was measured at 510, 530 and 755 nm for method A, B and C respectively against the reagent blank prepared in the same manner. The optimum experimental parameters for the color production are selected. Beer’s law is valid with in a concentration range of 4-20 μg mL-1 for method A, 7.5-37.5 μg mL-1 for method B and 5 -25 μg mL-1 for method C. For more accurate results, ringbom optimum concentration ranges are 5-18 μg mL-1 for method A , 8.5-35.5 μg mL-1 for method B and 6.0-23.0 μg mL-1 for method C. The molar absorptivities are 3.55x104, 2.10x104 and 3.10x104 L mol-1 cm-1. Where as sandell sensitivities are 0.024, 0.041 and 0.028 μg cm-22 for method A, B and C respectively. The mean percentage recoveries are 99.95 for method A, 101.35 for method B and 100.33 for method C. The developed methods were applied for the determination of PST in bulk powder and in the pharmaceutical formulations without any interference from tablet excipients.